Certified Information Security Manager Exam prep guide - Doshi, Hemang (Packt Publishing, 2022)
Master information security fundamentals with comprehensive explanations of concepts Purchase of the book unlocks access to web-based tools like practice questions, flashcards, and more to take your CISM prep to the next level Key Features Use this comprehensive resource to prepare for ISACA's CISM certification Unlock free online tools including interactive practice questions, exam tips, and flashcards to effectively prepare for the CISM exam Understand the theory behind information security program development and management Book Description CISM is a globally recognized and much sought-after certification in the field of IT security. This second edition of the Certified Information Security Manager Exam Prep Guide is up to date with complete coverage of the exam content through comprehensive and exam-oriented explanations of core concepts. Written in a clear, succinct manner, this book covers all four domains of the CISM Review Manual. With this book, you'll unlock access to a powerful exam-prep platform which includes interactive practice questions, exam tips, and flashcards. The platform perfectly complements the book and even lets you bring your questions directly to the author. This mixed learning approach of exploring key concepts through the book and applying them to answer practice questions online is designed to help build your confidence in acing the CISM certification. By the end of this book, you'll have everything you need to succeed in your information security career and pass the CISM certification exam with this handy, on-the-job desktop reference guide. What you will learn Understand core exam objectives to prepare for the CISM exam with confidence Get to grips with detailed procedural guidelines for effective information security incident management Execute information security governance in an efficient manner Strengthen your preparation for the CISM exam using interactive flashcards and practice questions Conceptualize complex topics through diagrams and examples Find out how to integrate governance, risk management, and compliance functions Who this book is for If you're an IT professional, IT security officer, or risk management executive looking to upgrade your career by passing the CISM exam, this book is for you. Basic familiarity with information security concepts is required to make the most of this book.